Land policies in India : promises, practices and challenges - Pellissery, Sony; Davy, Benjamin; Jacobs, Harvey M. (Springer, 2017)
This book examines how property rights are linked to socio-economic progress and development. It also provides a theoretical analysis, an economic/social analysis of planning, case studies of the implementation of planning and regulation instruments, practices related to law and planning, analysis of case laws in a particular segment. The interconnection between property, law and planning is a running theme throughout the book. The land question has been central to South Asian development on two counts: First, although the majority of the population relies on agriculture and allied activities their livelihood, landholding is highly skewed; second, urban planning is facing unprecedented challenges due to bourgeoning property values as well as gush of migrants to cities seeking livelihood. The response to these challenges in the form of laws and policies has been very large compared to the academic attention that is received. However, the measures emerging from planni ng and policies have had limited impact on the extent of the problems. This paradox calls for serious introspection and academic engagement that this book undertakes. The book further deals with the emerging discipline of planning law, which determines property value and use, and argues that regulatory issues of public policy determine the property valuation and property pricing.
Keywords: Land use -- Government policy -- India.; Land tenure -- India.; India.; elektronické knihy; electronic books